Cytotoxic Effect of Progesterone, Tamoxifen and Their Combination in Experimental Cell Models of Human Adrenocortical Cancer - Rossini, Elisa; Tamburello, Mariangela; Abate, Andrea; Beretta, Silvia; Fragni, Martina; Cominelli, Manuela; Cosentini, Deborah; Hantel, Constanze; Bono, Federica; Grisanti, Salvatore; Poliani, Pietro Luigi; Tiberio, Guido A. M.; et al. (Frontiers in Endocrinology, 2021)
Progesterone (Pg) and estrogen (E) receptors (PgR and ER) are expressed in normal and neoplastic adrenal cortex, but their role is not fully understood. In literature, Pg demonstrated cytotoxic activity on AdrenoCortical Carcinoma (ACC) cells, while tamoxifen is cytotoxic in NCI-H295R cells. Here, we demonstrated that in ACC cell models, ER were expressed in NCI-H295R cells, with a prevalence of ER-β over the ER-α.Metastasis-derived MUC-1 and ACC115m cells displayed a very weak ER-α/β signal, while PgR cells were expressed, although at low level. Accordingly, these latter were resistant to the SERM tamoxifen and scarcely sensitive to Pg, as we observed a lower potency compared to NCI-H295R cells in the cytotoxicity (IC50: MUC-1 cells: 67.58 µM (95%CI: 63.22–73.04), ACC115m cells: 51.76 µM (95%CI: 46.45– 57.67) and cell proliferation rate. Exposure of NCI-H295R cells to tamoxifen induced cytotoxicity r (IC50: 5.43 µM (95%CI: 5.18–5.69 µM) mainly involving ER-β, as their nuclear localization increased after tamoxifen: Δ A.U. treated vs untreated: 12hours: +27.04% (p<0.01); 24hours: +36.46% (p<0.0001). This effect involved the SF-1 protein reduction: Pg: - 36.34 ± 9.26%; tamoxifen: - 46.25 ± 15.68% (p<0.01). Finally, in a cohort of 36 ACC samples, immunohistochemistry showed undetectable/low level of ERs, while PgR demonstrated a higher expression. In conclusion, ACC experimental cell models expressed PgR and low levels of ER , in line with data obtained in patient tissues, thus limiting the possibility of a clinical approach targeting ER. Interestingly, Pg exerted cytotoxicity also in metastatic ACC cells, although with low potency.